Correlation of Parenting and Nutrient Intake with Stunting in Children 24-59 Months - Nelly SD Situmeang; Etti Sudaryati; Jumirah (Britain International for Academic Research (BIAR) Publisher, 2020)
Stunting is a chronic nutritional problem due to insufficient intake for a long time, in Indonesia the prevalence is high. The World Health Organization (WHO) classifies if the length/height z score is below −2 SD. The purpose of this study was to analyze the correlation between parenting, and nutrient intake (energy and protein) with stunting in children aged 24-59 years. This study used a cross sectional design with a sample of 117 children. Data collection was carried out with questionnaire instruments for parenting, and 24-hour food recall for nutritional intake. Data stunting was performed by comparing the height of the children measured by the WHO growth standards. Correlation analysis using Pearson correlation analysis. The results showed that the prevalence of stunting for children aged 24-59 months was 50.4%. There was a significant correlation between parenting with stunting (r = 0.287 and p = 0.02), energy intake with stunting (r = 0.215 and p = 0.020) and protein intake with stunting (r = 0.354 and p = 0.0001). It is recommended that the Ministry of Health improve nutrition surveillance programs, and encourage the community to monitor the growth of children under five years every month in health services.